Survey Of Traditional Fermentation Practices During Fufu Production In 3 LGAs In Ogun State And Potential Health Implications For Consumers - Elutade, F.B.; Ayo-Omogie, H. N. (Journal of Science, Technology and Innovation Research, 2025)
Cassava fermentation is a crucial process in fufu production, enhancing its texture, flavor and detoxification of cyanogenic compounds. However, variations in traditional fermentation practices, including the use of additives, raise concerns about food safety and quality. This study surveyed traditional fermentation practices employed during cassava fermentation for for fufu production in three Local Government Areas (LGAs) in Ogun State, Nigeria - Ijebu North, Ijebu East and Odogbolu. A survey was conducted among 54 local fufu processors to assess their demographic profile, fermentation methods, methods used to improve the sensory properties of fufu and additives being used. The results showed that all fufu producers were women, with majority (98.1%) aged between 31 and 50 years. Most (70.4%) had no formal education and all were self-employed. Submerged liquid fermentation was the dominant method (96.3%) being used, while 77.8% of the processors usually ferment for three days. Over half of the respondents (59.3%) use fermentation aids such as nails (37%), sandpaper leaves (Ficus exasperata) (11.1%) and Jatropha curcas leaves (9.3%) to accelerate the retting process, while 40.7% relied on natural fermentation without the use of aids. On methods used to improve the sensory properties, findings also revealed that 81.5% of respondents maintained good hygiene to control odour, while 14.8% used alum to improve colour. Additionally, 57.4% of the respondents identified bland flavour as the most acceptable, while 88.9% do not use additives to alter aroma. The findings highlight a reliance on indigenous knowledge for fufu fermentation, raising concerns about the safety of certain additives. The study recommends promoting awareness of safer fermentation techniques to ensure high-quality, health-compliant fufu production.